Anti-oxidative or anti-inflammatory additives reduce ischemia/reperfusions injury in an animal model of cardiopulmonary bypass - Salameh, Aida (Saudi J Biol Sci, 2020)
Severe inborn cardiac malformations are typically corrected in cardioplegia, with a cardio-pulmonary bypass (CPB) taking over body circulation. During the operation the arrested hearts are subjected to a global ischemia/reperfusion injury. Although the applied cardioplegic solutions have a certain protective effect, application of additional substances to reduce cardiac damage are of interest. 18 domestic piglets (10–15 kg) were subjected to a 90 min CPB and a 120 min reperfusion phase without or with the application of epigallocatechin-3-gallate (10 mg/kg body weight) or minocycline (4 mg/kg body weight), with both drugs given before and after CPB. 18 additional sham-operated piglets without or with epigallocatechin-3-gallate or minocycline served as controls. In total 36 piglets were analyzed (3 CPB-groups and 3 control groups without or with epigallocatechin-3-gallate or minocycline respectively; 6 piglets per group). Hemodynamic and blood parameters and ATP-measurements were assessed. Moreover, a histological evaluation of the heart muscle was performed. RESULTS: Piglets of the CPB-group needed more catecholamine support to achieve sufficient blood pressure. Ejection fraction and cardiac output were not different between the 6 groups. However, cardiac ATP-levels and blood lactate were significantly lower and creatine kinase was significantly higher in the three CPB-groups. Markers of apoptosis, hypoxia, nitrosative and oxidative stress were significantly elevated in hearts of the CPB-group. Nevertheless, addition of epigallocatechin-3-gallate or minocycline significantly reduced markers of myocardial damage. Noteworthy, EGCG was more effective in reducing markers of hypoxia, whereas minocycline more efficiently decreased inflammation. CONCLUSIONS: While epigallocatechin-3-gallate or minocycline did not improve cardiac hemodynamics, markers of myocardial damage were significantly lower in the CPB-groups with epigallocatechin-3-gallate or minocycline supplementation.